Contrast-enhanced Ocular Ultrasonography in Brachycephalic Dogs - Morato Abreu, Thais Guimaraes [UNESP]; Rossi Feliciano, Marcus Antonio [UNESP]; Maronezi, Marjury Cristina [UNESP]; Ramirez Uscategui, Ricardo Andres [UNESP]; Madruga, Gabriela Morais [UNESP]; Kobashigawa, Karina Kamachi [UNESP]; Crivelaro, Roberta Martins [UNESP]; Thiesen, Roberto; Laus, Jose Luiz [UNESP] (Univ Fed Rio Grande Do Sul, 2018)
Background: Contrast Enchantment Ultrasonography (CEUS) allows for detection of vascular flows that are difficult to detect with traditional methods. There were no reports found in the literature of the use of CEUS to evaluate the vascular pattern of the eye of brachycephalic dogs. The objective of this paper is to describe ultrasound findings observed in the eyes of healthy brachycephalic dogs subjected to CEUS. Materials, Methods & Results: Thirty adult brachycephalic dogs were subjected to physical, laboratorial, and ophthalmic examination. The eye structures were evaluated using CEUS after intravenous administration of Sonovue (R). Contrast enhancement was seen in 52 eyes with a homogeneous and centrifugal filling pattern. Structures adequately enhanced consisted of the optic nerve, the retina-choroid-sclera complex (RCSC), and the ciliary body. The optic nerve was hyperenhanced and the other structures were isoenhanced. The wash-in time, peak enhancement time, and wash-out time were similar for both right and left eyes. Mean values and standard deviation were calculated for contrast wash-in time, peak enhancement time, and wash-out time in the optic nerve, RCSC, and ciliary body. Discussion: Ultrasound is an important diagnostic resource for veterinary ophthalmology and provides relevant information for the detection of pathological conditions of the eyes of animals. The contrast-enhanced ultrasound allows evaluation of tissues at the capillary level (macro and microcirculation), complementing the vascular ultrasound scan. This study brings original information on contrast-enhanced ultrasound findings for evaluation of eyes in dogs, creating novel diagnostic possibilities for the use of this imaging technique in veterinary ophthalmology. The vascular pattern identified in this study, with enhancement starting at the region of the optic nerve and retina, and then ciliary body (with the optic nerve as the most hyperenhanced structure) is consistent with the expected pattern for dogs without ophthalmic disorders. The posterior ciliary artery is primarily responsible for supplying the optic nerve, later irrigating the retina, lateral and medial segments of the ciliary body. Some works on the evaluation of orbital vascular pattern in humans report a significant variability on anatomical course of the ophthalmic artery and its branches. However, in our study, no significant variation was observed on vascular flow of dogs of different brachycephalic breeds. Retinal blood vessels consist of arteries and veins that emerge from the optic nerve region and from the choroid. Contrast enhancement at the region of the RCSC is justified by the presence of vessels from the choroid that are irrigated by posterior ciliary arteries and drained by vorticose veins, since this structure is responsible for the nutrition of the external portion of the retina. Wash-in, peak enhancement, and wash-out times were similar for right and left eyes owing to anatomical and physiological similarities in vascularization. The homogeneous contrast-filling pattern is of paramount importance, since it will allow differentiation of abnormalities in sick animals, such as partial or total loss of capillarization, which will cause heterogeneity or absence of capillary fill. It will also be important for early diagnosis and evaluation of vascular alterations, especially ischemic changes, especially glaucoma, intraocular neoplasm, progressive retina atrophy, and uveitis. CEUS gives relevant information about the vascular pattern of the eyes of brachycephalic dogs, and is a quick, non-invasive, and safe exam.
Keywords: ciliary body; dog; ophthalmology; optic nerve; retina; vascularization